PKM POTENSI WAKAF UANG : PROSPEK, TANTANGAN DAN SOLUSI - Idel Waldelmi; Afvan Aquino; Aljufri Aljufri (Jurnal Abdimas Bina Bangsa, 2022)
The potential for cash waqf as the data reveals that cash waqf has great potential, this can be seen from the distribution of the population in Muslim Indonesia reaching 87.5%. However, in reality this potential is answered with data that only approximately 10% of Indonesian Muslim communities have endowments. That the potential of waqf is currently getting the attention of all groups, both private institutions, government, Islamic banking and other institutions. Knowledge, understanding and belief from the community about cash waqf will be a solution to the problems of the nation and state, the results of the implementation of training and seminars on the potential for cash waqf to be able to generate value that was unthinkable by the service team, but obtained from training and seminars directly from the waqf institution manager Indonesia (BWI) Riau representative. The occurrence of strong contributions from participants to be able to realize what is based on waqf management, both in knowledge, understanding and decisions results in a strong commitment to cash waqf